The outdoor office: a pilot study of environmental qualities, experiences of office workers, and work-related well-being - Söderlund, Carina; de la Fuente Suárez, Luis Alfonso; Tillander, Annika; Toivanen, Susanna; Bälter, Katarina (Frontiers in Psychology, 2023)
Outdoor office work is an emerging aspect of the concept of ‘new ways of working’, but only sparse data are available about the environmental qualities of the outdoor office space, experiences of office workers, and work-related well-being of outdoor office work. Here, we present an exploratory pilot study on well-being and outdoor office work in a public urban space. An outdoor office was set up in the courtyard of a university campus, and the participants (n = 16) conducted office work outdoors for 30 min and thereafter participated in an eye-tracking session for 11–15 min (n = 8) and subsequently filled out surveys (n = 16). The eye tracker allowed the discovery of natural and built elements in the outdoor environment that caught the participants’ visual attention, whereas the surveys assessed aspects of their subjective experiences of the outdoor office space (its visual and spatial qualities) and the work there. The results are presented as network graphs where correlations are shown regarding different aspects of office work outdoors. The results indicate that outdoor office work in a public urban space may promote work-related well-being in terms of positive outdoor office space experiences. Based on the findings, a preliminary set of outdoor office qualities is proposed. Those qualities relate to the legibility and imageability of the outdoor office space, its focal points, and depth/spaciousness, in addition to attributes of usability and environmental richness, including if the outdoor office space affords natural contact and supports activities, in addition to social and individual interactions and relations.